New insights into DEHP-induced inflammatory injury in chicken spleen: ROS/TLR4/MyD88 pathway and apoptosis/necroptosis-M1 polarization crosstalk - Yue Xu; Xiandan Zhang; Guangxing Li; Rong Guo; Hong Zhang; Bolin Zhao; Xiaoyu Zhao; Kaiting Chen; Xiaodan Huang (Poultry Science)
The environmental endocrine disruptor di(2-ethylhexyl) phthalate (DEHP) is a plasticiser used in large quantities in plastics and is hazardous to the health of humans and various animals. DEHP can be immunotoxic to the spleen through oxidative stress. Still, the role of splenic macrophage polarization in lymphocyte apoptosis and necroptosis, whether they interact with each other, and the mechanism of the effect on splenic inflammatory injury are unknown. In this study, based on the construction of a time-and dose-dependent model of DEHP-exposed chicken spleen, chicken lymphoma cell (MSB-1) and chicken macrophage (HD11) models were established to investigate the mechanism of apoptosis/necroptosis-M1 polarization crosstalk in DEHP-induced toxicity in chicken spleen injury. The results showed that DEHP exposure activated the ROS/TLR4/MyD88 pathway, up-regulated the expression of chemokines, induced macrophage M1 polarization, caused apoptosis and necroptosis in lymphocytes and inflicted inflammatory damage to the spleen, however, these effects could be alleviated by NAC. DEHP exposure of the HD11/MSB-1 cell co-culture system showed that M1 polarization promoted apoptosis and necroptosis and vice versa. In conclusion, DEHP exposure is involved in mediating the crosstalk between apoptosis/necroptosis and M1 polarization through the activation of the ROS/TLR4/MyD88 pathway, which in turn exacerbates inflammatory injury in the chicken spleen.